2008
DOI: 10.1096/fj.07-092981
|View full text |Cite
|
Sign up to set email alerts
|

A role for ceramide in driving cancer cell resistance to doxorubicin

Abstract: Advanced cancers acquire resistance to chemotherapy, and this results in treatment failure. The cellular mechanisms of chemotherapy resistance are not well understood. Here, for the first time, we show that ceramide contributes to cellular resistance to doxorubicin through up-regulating the gene expression of glucosylceramide synthase (GCS). Ceramide, a cellular lipid messenger, modulates doxorubicin-induced cell death. GCS catalyzes ceramide glycosylation, converting ceramide to glucosylceramide; this process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 60 publications
(62 reference statements)
6
158
0
Order By: Relevance
“…Altered composition of GSL and an increase in GL1 levels are characteristic of multidrug-resistant cancer cells such as KBV-1 and NCI/ADR-RES cells (5,33,34). Quantitative analysis of GCS and GM3S (GM3 synthase) mRNA levels by real-time PCR and measurement of GL1 levels by mass spectrometry confirmed KBV-1 cells exhibit increased expression of GCS and GM3S mRNAs and higher GL1 levels when compared to parental KB3-1.…”
Section: Exposure Of Drug-resistant Cancer Cells To Genz-123346 Lowersmentioning
confidence: 94%
“…Altered composition of GSL and an increase in GL1 levels are characteristic of multidrug-resistant cancer cells such as KBV-1 and NCI/ADR-RES cells (5,33,34). Quantitative analysis of GCS and GM3S (GM3 synthase) mRNA levels by real-time PCR and measurement of GL1 levels by mass spectrometry confirmed KBV-1 cells exhibit increased expression of GCS and GM3S mRNAs and higher GL1 levels when compared to parental KB3-1.…”
Section: Exposure Of Drug-resistant Cancer Cells To Genz-123346 Lowersmentioning
confidence: 94%
“…In adriamycin-resistant K562/AO2 cells, increased levels of Bcl-2 have been reported rather than that in sensitive K562 cells. Following the inhibition of GCS by PPMP or downregulation by siRNA transfection, decreased Bcl-2 gene expression levels have been reported [63]. Likewise, b-catenin-and cSrc signaling are responsible for the development of drug resistance due to increased levels of GCS in colon, cervical, breast, and ovary cancer cells that resist doxorubicin.…”
Section: Glucosylceramide Synthase In Drug Resistancementioning
confidence: 99%
“…pro-apoptotic sphingolipid metabolite, ceramide, is endogenously generated by chemo-or radio-therapies, [5][6][7] and exogenous short-chain ceramide has been shown to augment chemotherapy-induced cytotoxicity. [7][8][9] One of the exciting aspects of using ceramide as a chemotherapeutic is the preferential selectivity for inducing apoptosis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] One of the exciting aspects of using ceramide as a chemotherapeutic is the preferential selectivity for inducing apoptosis in cancer cells. For example, we previously demonstrated that nanoliposomal C 6 -ceramide induces cell growth arrest and apoptosis in breast cancer cells and melanomas, but not non-transformed mammary gland epithelial cells or melanocytes.…”
Section: Introductionmentioning
confidence: 99%